The Influence of Promotion, Perceived Ease of Use, and Price Toward Repurchase Intention Transportation Services Go-jek on Students in Universitas Negeri Padang - Aulia Restu Yohanda; Erni Masdupi; Yunita Engriani (Universitas Negeri Padang, 2019)
Purpose - The purpose of this research to analyze: (1) The influence of Promotion on Repurchase Intention Transportation Services Go-Jek On Students in Padang State University (2) The influence of Perceived Ease of Use on Repurchase Intention Transportation Services Go-Jek On Students in Padang State University (3) The influence of Price on Repurchase Intention Transportation Services Go-Jek On Students In Padang State University. Methodology - This type of research is descriptive research. The population in this study were all students at Padang State University User Go-Jek transportation services with a total sample of 170 people taken using convenience sampling because of the unknown population.Finding - Regarding the causal model proposed, the data confirm the relationship set out in the hypothesis. It can therefore be stated that ((1) Promotion significant effect on Repurchase Intention Transportation Services Go-Jek On Students in Padang State University (2) Perceived Ease Of Use significant effect on Repurchase Intention Transportation Services Go-Jek On Students In Padang State University (3) Price Use significant effect on Repurchase Intention Transportation Services Go-Jek On Students In Padang State University.Limitation - This research only limit with some variables Keywords: Promotion, Perceived Ease Of Use, Price and Repurchase Intention